Postharvest Management of Anthracnose on Quality of Papaya (Carica Papaya l.) Using Antagonistic Bacteria - Rahman, Md. Atiqur (2008)
A study was conducted to evaluate the biocontrol potential of antagonistic bacteria to manage anthracnose disease and postharvest quality of papaya during storage. The fruits of papaya cv. ‘Sekaki’ were found to be highly susceptible to several postharvest fungal diseases. Among them, anthracnose caused by Colletotrichum gloeosporioides was the most prevalent, where disease incidence and severity was recorded as 90-98 and 25-38%, respectively. This fungus was isolated from naturally infected papaya fruits and confirmed as pathogenic to papaya fruits. Epiphytic bacteria, isolated from leaf and fruit surfaces of papaya were tested as biocontrol agent against C. gloeosporioides. From 27 antagonistic bacteria screened in vitro by dual and concomitant test, four isolates namely B23, B19, B04 and B15 had high antagonistic activities against the test fungus. Using the Biolog system, isolates B23 and B19 were identified as Burkholderia cepacia, and B04 and B15 as Pseudomonas aeruginosa. Both B. cepacia and P. aeruginosa strongly inhibited the fungal growth by an average of 74 and 68%, respectively. However, B. cepacia strain B23 was found to be the most efficacious biocontrol agent in this study, since both cell suspension and filter sterilized culture filtrate of this bacterium completely suppressed the spore germination of the test fungus, which P. aeruginosa could not. These suggest that an antibiotic substance (s) may be produced by B. cepacia B23. Effect of different culture media on the production of antifungal substances by B. cepacia B23 was investigated to improve the efficacy of this biocontrol agent. The bacterium grew faster in nutrient broth medium and the cell concentration in this liquid medium reached the highest level (Log10 15.7 CFU mL-1) after 72 h of inoculation. Consequently, this bacterium produced more antifungal substances in nutrient broth than other tested media. Higher dilution (1:8) of the antifungal substances in crude supernatant from B. cepacia B23 was found to inhibit the mycelial growth and spore germination of C. gloeosporioides by 41 and 100%, respectively. Pyrrolnitrin and three other unidentified antifungal compounds were detected on TLC plates, which were resistant to boiling and autoclaving at 121 °C for at least 20 min. This bacterium was found to be highly compatible with chitosan (0.75%) and calcium chloride (3%) or mixture of both. Both of these chemicals have suppressive activity against C. gloeosporioides of papaya and could be used as enhancer of biocontrol efficacy of B. cepacia B23 during storage. The survival and proliferation of B. cepacia B23 in papaya wounds and on fruit surfaces was not affected by chitosan-CaCl2 throughout the storage period. The combination of B. cepacia B23 with chitosan-CaCl2 was more effective in controlling the disease than B. cepacia B23 alone or other treatments both in inoculated and naturally infected fruits. Combining B. cepacia B23 with chitosan-CaCl2 gave the complete control of anthracnose in artificially inoculated fruits stored at 14 ºC and 95% RH for 18 days, which was equal to that obtained with fungicide benocide® (benomyl 50% WP). However, this combination offered a greater control by reducing 99% disease severity in naturally infected fruits at the end of 14 days storage at 14º C and 95% RH plus six days post ripening at 28 ± 2 ºC, which was superior to that found with benocide® or other treatments tested. Furthermore, fruits treated with the combination of B. cepacia B23-chitosan-CaCl2 showed delayed climacteric respiration and ethylene evolution by at least 7 days compared to control with reduced rate of CO2 and C2H4 production. This combined treatment reduced weight loss by more than 25% compared to the control. It also markedly slowed down the ripening of fruits as shown by their retention of firmness 4.17 Newton (N) after storage. Moreover, a delayed change in external colour, titratable acidity and pH without compromising fruit quality was observed in fruits that were subjected to the combined treatment. The storage life was thus extended up to 15 days when compared with control. In addition, the incorporation of 3% CaCl2 into the combined treatment significantly increased (81%) the calcium content in fruits compared to control, thus resulting in improved the nutritional value of the papaya. This study provided an alternative method for fungicides treatment of papaya at postharvest.